Status and Development of Agricultural Public-Private Partnership Program Implementation in China - Qiliang Hu; Harry Entebang; Chin-Hong Puah (Caraka Tani: Journal of Sustainable Agriculture, 2024)
As the initiator of the Belt and Road Initiative, the Chinese Government’s goal in agriculture is to promote the sustainable development of agriculture throughout China and the world. One of the feasible ways to realize this goal is to adopt the Public-Private Partnership (PPP) model. This study aims to analyze the current status of agricultural PPP projects in China and their impacts. This study utilized the Ministry of Finance database to collect 2014 to 2022 data on agricultural PPP projects in China. The collected data were organized and analyzed to analyze the current situation and return mechanism of Chinese agricultural PPP projects. The results show that China’s agricultural PPP projects are less attractive than other sectors, government and social-private sector cooperation is less sustainable, and laws and regulations and risk assessment are not well developed. Therefore, this study proposes to promote the development of agricultural PPP projects by standardizing the law, improving the return mechanism, and strengthening the risk assessment. Thus, it further promotes the sustainable development of agriculture and plays a certain positive role.